P207 Outcomes from acute NIV: are british thoracic society quality standards realistic?. (December 2018) - Burns, JE; Faulkner, J; Brabbs, R; Hornsby, J; Lowe, D; Carlin, C
Abstract : Background: Acute non-invasive ventilation (NIV) for life-threatening acidotic exacerbations of COPD is an effective treatment, with a number needed to treat of 8 to prevent 1 death in Cochrane meta-analysis. Recent NCEPOD publication highlighted shortfalls in UK acute NIV practice with poorer outcomes, resulting in publication of UK Quality Standards for Acute NIV. The evidence-base for some of these is limited, ability to achieve these standards is uncertain and it is unclear whether impaired acute NIV outcomes reflect shortfalls in care, case-mix of patients in routine practice, or a combination. We have established an acute NIV audit, quality improvement and innovation programme to address these issues, and can present the first dataset from this. Methods: Fifty acute NIV episodes were identified from resuscitation room and acute respiratory unit records. Data was reviewed using NCEPOD audit toolkit with analysis of inter-rater agreeability between two data to evaluate the toolkit's reliability. Inpatient mortality and readmission rates was also noted. Results: Incomplete recognition of patients receiving acute NIV was noted. Performance against two NCEPOD recommendations was graded green (100% compliance), three amber (50%–99%), and five red (0%–49%). Inter-rater agreeability with NCEPOD audit tool was low. ABG sampling during NIV (50% at 30–90 mins, 44% at 3–5 hours) was inconsistent. 38.8% of individuals were judged to have received suboptimal NIV. Inpatient mortality was 32.0% overall (vs 10% in Cochrane review) but there was no improvement in those who received optimal NIV. 6 month readmission rates (61.8%, of whom 28.6% were within 2 weeks) and mortality rates (32.4%) were similar to national published data. Conclusions: The validity of the NCEPOD toolkit and UK Acute NIV Quality Standards is questioned based on the subjectivity of some toolkit variables, low inter-rater agreeability, limited evidence base and lack of consideration for realistic medicine and documentation challenges. High mortality and readmission rates in this cohort emphasise a need to standardise and improve management of patients with hypercapnic respiratory failure. Lack of improvement in overall outcome of patients judged to have had optimal acute NIV suggests that striving to achieve NCEPOD derived standards may not address these challenges.